2018
DOI: 10.1016/j.psyneuen.2018.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of Gender Dysphoria: androgen and estrogen receptor interaction

Abstract: ERβ plays a key role in human gender differentiation in males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 34 publications
1
53
0
1
Order By: Relevance
“…On the other hand, these data are also consistent with our previous genetic data on the participation of the ESR1 gene in the genetic basis of gender dysphoria. 30,31 Here, we propose that variations in RIII methylation are related to the process of masculinization of the brain and, therefore, to the etiology of gender incongruence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these data are also consistent with our previous genetic data on the participation of the ESR1 gene in the genetic basis of gender dysphoria. 30,31 Here, we propose that variations in RIII methylation are related to the process of masculinization of the brain and, therefore, to the etiology of gender incongruence.…”
Section: Discussionmentioning
confidence: 99%
“…It might be related to neurodevelopmental processes of the brain 19,21 probably as a consequence of a genetic vulnerability 22e32 that implicates variations in the nuclear receptor's sensitivity to their ligand. In our previous studies, 31 we first proposed a hypothetic genetic model based on ERa, ERb, and AR allele combinations. We suggested that different allele combinations could modulate the sensitivity and therefore the efficiency of the ER to the ligand, and thus, different ERa, ERb, and AR allele combinations may play a significant role in brain masculinization.…”
Section: Introductionmentioning
confidence: 99%
“…The TG biological underlining is not well understood. Genetically, it appears that interplay between sex steroid receptor polymorphisms, particularly those of androgen and estrogen, which are associated with TG [3]. Yet the RYR3 variant was identified in the Han Chinese population with GD [4] and CYP17 single nucleotide polymorphism was linked to female-to-male TGism [5] whereas a common SRD5A2 polymorphism has been shown recently to be benign in TGism (ClinicalTrials.gov Identifier: NCT00435513).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence GI has increased in recent years, possibly because of the increased visibility and destigmatization of this condition. A recent study reported that 4.6 people per 100,000 hav (Fernández, et al, 2018)e GI, with about 6.8 males-to-females (MtFs) and 2.6 females-to-males (FtMs) per 100,000 people .…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of GI is uncertain; however interactions among biological, environmental, and cultural factors are likely to be important (Rosenthal, 2014). Recent research suggested that polymorphisms of estrogen and testosterone receptors and of enzymes involved in the metabolism of these hormones have roles in the etiology of GI (Kudwa, Michopoulos, Gatewood, & Rissman, 2006;Raznahan, et al, 2010;Henningsson, et al, 2005;Fernández, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%